Determination of vanadium in human hair slurries by electrothermal atomic absorption spectrometry - Fernandes, Kelly G.; Nogueira, Ana Rita A.; Gomes Neto, José Anchieta [UNESP]; Nobrega, Joaquim A. (Elsevier B.V., 2007)
This work describes an analytical procedure for vanadium determination in human hair slurries by electrothermal AAS using longitudinal heating (LHGA) and transversal heating (THGA) graphite furnace atomizers. The samples were powdered using cryogenic grinding and the hair slurries containing 0.2% (m/v) were prepared in three different media for determination of vanadium: 0.14 mol L-1 HNO3, 0.1% (v/v) Triton X-100 and 0.1% (v/v) water soluble tertiary amines (CFA-C, pH 8). The limits of detection (LOD), limits of quantification (LOQ), and characteristic masses obtained were 0.28, 0.95 mu g L-1 and 35 pg (LHGA) and 0.34, 1.13 mu g L-1 and 78 pg (THGA), respectively. The accuracy of the analytical results obtained by the proposed procedure in both equipments was confirmed by a paired t-test at the 95% confidence level and compared with a conventional procedure based on acid digestion. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: vanadium; human hair; slurry sampling; graphite furnace AAS; LHGA; THGA